Effects of 2-deoxyglucose, glucosamine, and mannose on cell fusion and the glycoproteins of herpes simplex virus. - Knowles, R W (1976)
2-Deoxyglucose and glucosamine were found to inhibit cell fusion caused by a syncytial mutant of herpes simplex virus and to inhibit the glycosylation of viral glycoproteins in the infected cells. The inhibition of fusion and the inhibition of glycosylation caused by 2-deoxyglucose were substantially prevented when mannose was also present during infection. When glycosylation was inhibited, three new bands were found in major glycoprotein region on sodium dodecyl sulfate-polyacrylamide gels. These bands may be precursors to the normal glycoproteins. The correlation between fusion and glycosylation in the presence of 2-deoxyglucose, glucosamine, and mannose suggests that the cells cannot fuse if their glycoproteins have a considerably reduced carbohydrate content.